Nasdem's Party Victory in West Java Local Leader Election 2020 - Arlan Siddha (Universitas Sultan Ageng Tirtayasa, 2022)
This journal examines the Nasdem Party's campaign strategy in the 2020 Simultaneous General Elections in West Java Province. The election of all Candidate Pairs promoted by the Nasdem Party in five regions in West Java is a proud success, especially during this Pandemic because political campaign and marketing strategies are needed which are certainly different from usual. Theoretically, the victory of Nasdem is analyzed through a campaign strategy with four marketing indicators known as the 4Ps, namely Product, Price, Place, and Promotion. Methodologically, this journal uses a qualitative approach to case studies and literature studies. The data collection technique was carried out using primary data and secondary data taken from journals, online news, both news from television and news from online media, as well as KPU releases regarding data on the results of the 2020 Regional Head Elections. The findings of this study are that the victory of the NasDem Party is highly dependent on Price, Promotion, and Product factors. The five pairs of candidates promoted by NasDem are highly invested candidates, both in terms of campaign financing and in terms of promotion. In addition, the victory achieved by the NasDem Party cannot be separated from the character of the candidates promoted by the Nasdem Party, most of these candidates are candidates who are well known to the public, such as incumbents and former Indonesian actors, and candidates who have extensive networks such as businessmen.